Kesiapsiagaan Masyarakat dalam Menghadapi Ancaman Kebakaran - Ananda Mutia Hasna; Siti Dahlia; R. Tricahyono Nur Harsono; Agung Adiputra (Universitas Negeri Gorontalo, 2023)
Fire disasters still occur frequently so that people are encouraged to have knowledge of preparedness in anticipating fire disasters. However, information about the community's ability to anticipate fire disasters is still very limited. The research objective was to determine community preparedness in facing the threat of fire in Penggilingan Village, Cakung District, East Jakarta. The method used is descriptive research using quantitative data. The study population consisted of all heads of households living in Penggilingan sub-district, totaling 40,641 families, while the sample was part of the heads of families, totaling 125 families. Sampling used proportional random sampling technique. The research variable was community preparedness in facing the threat of fire as measured by 4 parameters from LIPI-UNESCO/ISDR, 2006 namely knowledge and attitude, disaster warning system, emergency response plan, and ability to mobilize resources. Data were analyzed using frequency distribution tables and preparedness indexes. The results showed that the community is prepared to face the threat of fire in Penggilingan Village, Kec. Cakung is categorized as ready with an index value of 79.03. Even though it is in the ready category, it would be better if this preparedness continues to be improved to become very ready. Especially preparedness regarding the disaster warning system and the ability to mobilize resources that still need to be evaluated by the community and stakeholders. As well as fire socialization or training programs should be further intensified so that information about fire disasters can be received by all levels of society.